2016
DOI: 10.1109/tdei.2015.005407
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of insulation performance of solid/gas composite insulation with embedded electrode

Abstract: Solid insulated switchgear (SIS) has been developed as a substitution for medium voltage sulfur hexafluoride (SF6) gas insulated switchgears. Its main circuit including a vacuum interrupter is coated with epoxy resin. Therefore, a solid/gas insulation system is composed. For further miniaturization and higher stress design of SIS, improvement of the insulation performance is required. In the solid/gas insulation system, the breakdown strength along the surface is lower than that of solid. Then, the authors inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…In the previous study [4], the authors measured the surface breakdown voltage (BDV) and the partial discharge inception voltage (PDIV) under ac or impulse voltage application. The measurement was done by changing the radius of the embedded electrode ( e ), thickness of the disc-shaped epoxy resin plate ( ) or the radius of the epoxy resin plate ( p ).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study [4], the authors measured the surface breakdown voltage (BDV) and the partial discharge inception voltage (PDIV) under ac or impulse voltage application. The measurement was done by changing the radius of the embedded electrode ( e ), thickness of the disc-shaped epoxy resin plate ( ) or the radius of the epoxy resin plate ( p ).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study [3], the authors investigated on the surface breakdown voltage (BDV) and the partial discharge inception voltage (PDIV) by varying the radius of the embedded electrode ( e ), thickness of the disc-type epoxy resin plate ( ) or the radius of the epoxy resin plate ( p ) under ac or impulse voltage application. As a result, it was found that the surface discharge initiated at the point of the maximum electric field strength along the surface and it propagated in both directions towards the center rod electrode and towards the ground electrode.…”
Section: Surface Breakdown Modelmentioning
confidence: 99%
“…Equation A model of composite insulation system with embedded electrode. p is the radius of the disc-type epoxy resin plate, e is the radius of the embedded electrode and is the thickness of the epoxy resin plate [3].…”
Section: Surface Flashover Characteristics Onmentioning
confidence: 99%
See 2 more Smart Citations